PANTI SOSIAL PEMBINAAN TUNANETRA DAN TUNADAKSA DI KELURAHAN KELAYAN BARAT - Gusti Muhammad Irsyad Maulana; Nursyarif Agusniansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
People with disabilities in Banjarmasin, particularly in the Kelayan Barat sub-district, face various challenges in their daily lives. It has been found that stigma and lack of awareness among the community regarding the needs and rights of people with disabilities have a negative impact on their lives, including affecting their independence and self-confidence to participate in society. In order to improve their independence and self-confidence, specific guidance and support for people with disabilities are needed, aiming to foster self-reliance, confidence, and productivity, enabling them to contribute to society. To achieve this ultimate goal, the establishment of training and mentoring centers utilizing the Universal Design method is necessary. The implementation of Universal Design in buildings can address the crucial aspect of accessibility, which is often a primary challenge faced by individuals with disabilities in carrying out their activities. Coupled with programs that enhance productivity, such as skills training and handicraft workshops, over time, self-confidence and independence can gradually be developed.